PENGARUH MODEL PEMBELAJARAN PBL TERHADAP HASIL BELAJAR DAN KECERDASAN EMOSIONAL SISWA KELAS V MATA PELAJARAN MATEMATIKA - Dwi, Dhevi Dwi Anggraini; Prihatiningtyas, Nindy Citroresmi; Rosmaiyadi (Universitas Negeri Medan, 2025)
Many students tend to give up easily when faced with Mathematics lessons. This has an impact on less than optimal learning outcomes. One of the main causes is the low self-confidence of students in understanding and solving mathematics problems, so they are afraid of failing and reluctant to try. Lack of self-confidence in their own abilities makes students unmotivated to learn optimally. Therefore, this study aims to determine whether there is an influence and difference in learning outcomes and emotional intelligence of students taught with the PBL model and the contextual model and how it is implemented at SDIT Nurul Islam Singkawang. This study uses a quantitative approach involving grade V students. Data collection was carried out through pretest, posttest and questionnaire questions. The results of this study indicate that differences in student learning outcomes are caused by PBL steps that have a positive influence by placing students as active subjects of learning, while differences in students' emotional intelligence are caused by the PBL model which provides space for students to express themselves and provide influence because the characteristics of PBL are in line with indicators of emotional intelligence.